Evidence for FHL1 as a novel disease gene for isolated hypertrophic cardiomyopathy - Friedrich, Felix; Wilding, Brendan R.; Reischmann, Silke; Crocini, Claudia; Lang, Patrick; Charron, Philippe; Müller, Oliver J.; McGrath, Meagan J.; Vollert, Ingra; Hansen, Arne; Linke, Wolfgang A.; Hengstenberg, Christian; et al. (Human molecular genetics, 2012)
Abstract. Hypertrophic cardiomyopathy (HCM) is characterized by asymmetric left ventricular hypertrophy, diastolic dysfunction and myocardial disarray. HCM is
Gesehen am 09.05.2018